Aspects of the interaction of pectin-coated Ag nanoparticles with methylene blue with regard to photodynamic applications - Hileuskaya, Kseniya; Ihnatsyeu-Kachan, Aliaksei; Kraskouski, Aliaksandr; Saichuk, Anastasiia; Hileuskaya, Aliaksandra; Nikalaichuk, Viktoryia; Kulikouskaya, Viktoryia; Kim, Sehoon (Elsevier BV, 2023)
The promising future of photodynamic therapy has led to progress in the design of highly effective new -generation photosensitizers based on the combination of plasmonic metal nanoparticles and fluorescent mole-cules to kill cancer cells and bacteria. In this work, the details of the interaction of pectin-coated Ag nano -composites (NCs) of different sizes (8, 10, 13, and 28 nm) and various types of pectin shells with the classical photosensitizer methylene blue (MB) were investigated. Pectin-Ag NCs were characterized by UV-vis spectros-copy, DLS, TEM, and XPS. The enhanced singlet oxygen generation effect of pectin-Ag@MB complexes was size -dependent (the smaller the size of the plasmonic particles, the higher the 1O2 generation) and associated with the local concentration of the dye in different molecular forms in the pectin shell of nanoparticles. In cell experi-ments, the pectin-Ag@MB complexes did not show enhanced phototoxicity or cellular uptake towards cancer cells, compared to free MB. The prolonged release of MB from the complex in a phosphate-buffered saline so-lution (pH 7.4) was observed. The amount of irreversibly bound MB depended on the type of pectin shell and equaled 1.13, 1.45, and 2.57 mu g per mg pectin for Citrus25-Ag, Classic25-Ag, and Classic10-Ag NCs, respectively. The obtained physicochemical insights supplement the present understanding of the fundamental aspects of the interaction between plasmonic polymer-capped nanoparticles and MB and could be important for the rational design of new theranostic agents.